(untitled) (Journal of the College of Basic Education, 2026)
Most of Sabiq al-Barbari’s poetry deals with asceticism and wisdom, and the ascetic poet is no different from others in his interest in this artistic aspect. The title of the research is (Sabiq al-Barbari’s Poetry: A Rhetorical Study). It is based on a summary, an introduction, and three sections. The first section deals with the imperative styles (command, prohibition, interrogation, and calling) and the analysis of some poetic verses of these styles. The second research deals with the rhetorical styles (simile, Metaphor, metonymy) and an analysis of some poetic verses using these techniques. The third section deals with rhetorical devices (alliteration, alliteration) and an analysis of some poetic verses using these techniques. This research was supported by multiple sources and references, including books on literature and rhetoric.